Pelatihan Analisis Data Organisasi Dengan Menggunakan AI Untuk Pengambil Keputusan Bagi Pengurus JPRMI Jakarta (Jaringan Pemuda Dan Remaja Mesjid Indonesia) - Sita Anggraeni; Syaifur Rahmatullah; Achmad Rifai (CV. Multi Kreasi Media, 2026)
Conventional decision-making methods, which rely on intuition, past experience, and simple spreadsheet analysis, are proving increasingly inadequate. These approaches are limited in their ability to identify complex and hidden patterns within massive datasets. As a result, many organizations find themselves stuck making reactive, suboptimal, and even high-risk decisions, which can ultimately erode their competitive advantage. There is a significant gap between the potential of the data available and an organization’s ability to translate it into smart strategic decisions. The use of AI can analyze and modify the decision-making process by improving the efficiency and accuracy of information available to leaders, as well as assessing its impact on the quality of decisions made. This allows us to identify the challenges and obstacles leaders may face when implementing AI in decision-making, as well as strategies that can be applied to overcome these challenges. Ultimately, AI can provide practical recommendations for leaders and organizations on the best ways to leverage AI in the strategic decision-making process. The objective of this training is to develop skills in reading and analyzing organizational data using AI, as well as to understand the steps involved in quickly and accurately reading and analyzing organizational data using AI to support decision-making for the administrators and members of the Indonesian Mosque Youth and Teen Network (JPRMI).